Intellect and the One in Porphyry's Sententiae - DILLON, JOHN MYLES (Elsevier, 2010)
This article seeks to provide some support for the troublesome report of Damascius in the De Principiis that, for Porphyry, the first principle is the Father of the Noetic Triad?and thus more closely implicated with the realm of Intellect and Being than would seem proper for a Neoplatonist and faithful follower of Plotinus. And yet there is evidence from other sources that Porphyry did not abandon the concept of a One above Being. A clue to the complexity of the situation may be provided by a passage from Proclus (In Parm. 1070, 155ff. Cousin) which criticises him for making the One the subject also of the Second Hypothesis of the Parmenides. Here, I consider a series of passages from Porphyry's Sententiae which seem to indicate a doctrine of the One essentially faithful to that of Plotinus, but modulated in the direction of closer linkage to the levels of reality below it.
PUBLISHED
Keywords: Philosophy; Plotinus